Ts. Dr. Nasrul Hadi produces Protective Bandana (Pro-B) reducing the risk of injury to takraw players - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 4 September 2023 - Sepak takraw is one of the sports that has the potential to bring medals to Malaysia, but it is only contested up to the Asian Games level.